Il Remote Sensing per l'individuazione delle Zone di Gestione nei vigneti - Mattioli, Elisabetta; Antognelli, Sara; Natale, Antonio; Sartoretti, Velia (GEOmedia, 2018)
Spatial variability inside a vineyard has been always difficult to be measured in order to valorize the enological potential of the grapes. Remote Sensing is a technique that can be used for improving wine quality through the identification of Management Zones in the fields and the consequent differential grape harvest. The technique is based on the use of Vigor Vegetation Indices, that allow to identify the variations of the grape growth and the composition of the grape in the vineyard, and the changes that happen over time. Agricolus software provides these features and it has been used successfully in some vineyards in the center of Italy.